Data analysis of Q-value measurements for double-electron capture with SHIPTRAP - Roux, Christian-Eric; Blaum, Klaus; Block, Michael; Droese, Christian; Eliseev, Sergey; Goncharov, Mikhail Leonidovich; Herfurth, Frank; Ramirez, Enrique Minaya; Nesterenko, Dmitry Alexandrovich; Novikov, Yuri Nikolaevich; Schweikhard, Lutz (The European physical journal. D, Atomic, molecular, optical and plasma physics, 2013)
A measurement campaign has been carried out for the search for resonantly enhanced neutrinoless double-electron-capture transitions by the determination of the Qεε-values with the SHIPTRAP Penning-trap mass spectrometer. The Qεε-values have been determined by measuring the cyclotron-frequency ratios of the mother and daughter nuclides of the transitions. This article describes the experimental approach and the data analysis by the example of neutrinoless double-electron capture in 152Gd. Various effects as, e.g., temporal fluctuations and spatial inhomogeneity of the magnetic field, or the variation of the ion number in the trap were found not to affect the frequency ratio on the 1 ppb-level, which is the present statistical uncertainty.